Parallel Image-Based Visual Servoing/Force Control of a Collaborative Delta Robot - Zhu, Minglei; Huang, Cong; Qiu, Zhiqiang; Zheng, Wei; Gong, Dawei (Frontiers in Neurorobotics, 2022)
In this paper, a parallel Image-based visual servoing/force controller is developed in order to solve the interaction problem between the collaborative robot and the environment so that the robot can track the position trajectory and the desired force at the same time. This control methodology is based on the IBVS dynamic computed torque control and couples the force control feedback in parallel. Simulations are performed on a collaborative Delta robot and two types of image features are tested to determine which one is better for this parallel IBVS/force controller. The results show the efficiency of this controller.